Patient safety culture in critical and non-critical areas: a comparative study - Alessandra Suptitz Carneiro; Graziele de Lima Dalmolin; Tânia Solange Bosi de Souza Magnago; Laura Prestes Moreira; Eduarda Dalla Costa; Rafaela Andolhe (SciELO, 2021)
ABSTRACT Objective: to compare the perception of patient safety culture among health workers from critical and non-critical areas. Method: cross-sectional study with health workers from critical and non-critical areas of a large hospital. Data collection used a characterization instrument and the Safety Attitudes Questionnaire. The analysis was performed in the Predictive Analytics Software Statistic®. Results: a total of 393 workers participated, predominantly women, over 43 years old, nursing technicians, with a partner, and children. Results indicated that the areas have a negative perception of patient safety (66.5%, ±12.7 critical; 63.5%, ±14.4 non-critical). Only job satisfaction had a positive score (83.0%, ±15.9 critical; 80.1%, ±17.5 non-critical). There was a relationship between being a worker in critical areas and having a positive perception of the unit's management (p = 0.041). Conclusion: both areas have a negative perception of the safety culture. Although critical areas have obtained more positive evaluations, the results did not show statistical significance when compared to non-critical areas.